Research on the influence of the economic development of the importing country on export of new energy Vehiclesof China – based on the empirical analysis of countries along the belt and road - Wang, Wenjuan; Xie, Dongcheng (Edelweiss Applied Science and Technology, 2025)
In today’s era, severe environmental problems and the energy crisis have prompted the global pursuit of green development. New energy vehicles have become a key area in international trade. For China, their exports are crucial to its "two-carbon" goal and to upgrading its auto industry. The Belt and Road Initiative offers a vast market, but there are economic differences among participating countries. This study first sorted out relevant literature and theories, and then theoretically discussed the impact of the economic level of the importing country on the export of new energy vehicles along the "Belt and Road" in China. Using the trade gravity model and 2017-2022 export data, the two-way fixed-effect model is used to analyze the impact of the GDP of the importing country, and the heterogeneity is analyzed by income level. An intermediate variable, the market share of electric vehicles in the importing country, is introduced to further explore its internal mechanism. The results show that the growth of GDP and per capita GNI in the importing country significantly promotes China’s NEV exports, and the economic level of a country affects residents’ acceptance and consumption willingness, thus affecting China’s exports from the demand side.